Análise da expressão gênica de proteinases cisteínicas relacionadas à morte celular programada e à maturação de proteínas de reservas em sementes de pinhão manso (Jatropha curcas L.). - Rocha, Antônio José (2012)
Jatropha (Jatropha curcas L) is an oilseed plant with great potential for biofuel production because of the wealth of existing lipids in their seeds. Therefore, it is a potential source of renewable oil that has received considerable attention from the scientific community. The objective of this study was to analyze the gene expression of cysteine ​​proteinases related to programmed cell death (PCD) in developing seeds and during germination of Jatropha in order to better understand the transcriptome of the major genes involved in the MCP and during the deposition of protein reserves during maturation of seeds of Jatropha. To accurately quantify the levels of gene expression by RT-qPCR was necessary to make a selection of reference genes (genes constituting). The constituent genes chosen for this study were: Glyceraldehyde-3-phosphate dehydrogenase (GAPDH), polyubiquitin (PUB), alpha-tubulin (TA2), protein phosphatase 2 A (PP2A2), elongation factor-alpha (EF1-α) and actin, all cited in the literature and were chosen for study standardization of genes into plants. Through the program of geNorm was possible to show the more stable reference genes among the six genes of reference. Our results indicate that the most stable reference genes for samples of the developing endosperm and integument were: GAPDH, PP2A2 and EF1-α and TA2. The genes were less stable: the actina11; polyubiquitin (PUB). In germination, the most stable genes were GAPDH, PUB and TA2. However, genes with lower stability values ​​were actin, EF1-α and PP2A2. In our studies, the geNorm program also showed the number of reference genes needed for normalization of data obtained by RT-qPCR. In the analysis of this study, we show that for the developing seeds, the use of four most stable genes were GAPDH, PP2A2 and EF1-α and TA2 needed for normalization of RT-qPCR data. In the data of germinating seeds, was the adoption of more stable three genes (GAPDH, PUB and TA2). However, To validate our findings with reference genes, we used the standard profile of gene expression which expresses oleosina, which showed that the expression pattern of oleosina is provided according to the literature, genes reveals that the reference are efficient to normalize the data obtained by RT-qPCR. With these results, we carried out a study of expression of genes supposedly involved in programmed cell death and maturation of seeds of Jatropha. Our results showed that genes with sequence C-terminal KDEL: JcCB0580861; JcCA0152821; JcCA0047111 and γ-VPE gene JCCB0060111 showed high levels of expression in later stages in tissues of the integument and endosperm of seeds of Jatropha in developing and Based on our analysis, these genes express cysteine ​​proteinases that are possibly involved in the MCP. Nevertheless, genes that express the following VPEs: JcCB0196871; JcCB0244081, and JcCA0012422 according to our studies, are probably involved in the maturation of protein reserves in developing seeds of Jatropha. These data provided important information about the expression pattern of genes that are involved in the transcriptome of developing seed, more specifically involved in the process of MCP. However, the study of standardization and validation of reference genes in tissues of the integument and endosperm Jatropha provided a better understanding as regards the stability of these genes in the studied conditions.